Beyond Stamp Collecting: Ronald Coase and “Scientific” Legal Scholarship - John N. Drobak (Washington University Journal of Law & Policy, 2017)
This Essay argues that legal scholarship is properly considered a highly technical field of study rather than a system based on classifications. Drobak concedes that excellent legal scholarship requires a complex system of classifications akin to “stamp collecting.” Drobak then makes a case for legal research as a technical science requiring an interdisciplinary approach to confront new issues and further develop current legal doctrines.
Keywords: legal scholarship; legal research; technical science; Ronald Coase